2015
DOI: 10.11138/ccmbm/2015.12.3s.021
|View full text |Cite
|
Sign up to set email alerts
|

Algodystrophy (CRPS) in minor orthopedic surgery

Abstract: Algodystrophy or Chronic Regional Pain Syndrome (CRPS) is a painful disorder that develops especially at upper or lower extremities of the limbs after a fracture. This syndrome is probably due to bone microvascular changes with subsequent sympathetic nervous system involvement. The pain that characterizes CRPS is spontaneous, disproportionate to the traumatic event and is associated with hyperalgesia, and a variety of autonomic and trophic disorders. This condition has a variable incidence up to 37% of the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…12 This delay in diagnosis is the major cause of a high percentage of chronic pain and complication of functional impairment. 5 It has also been reported that early diagnosis associated with remission in 80%-90% of the cases. 12 Our study included 6 questions that were used to assess the awareness about CPRS, with 4 questions were only for those who have seen this condition before and used diagnostic criteria.…”
Section: Internistsmentioning
confidence: 95%
See 4 more Smart Citations
“…12 This delay in diagnosis is the major cause of a high percentage of chronic pain and complication of functional impairment. 5 It has also been reported that early diagnosis associated with remission in 80%-90% of the cases. 12 Our study included 6 questions that were used to assess the awareness about CPRS, with 4 questions were only for those who have seen this condition before and used diagnostic criteria.…”
Section: Internistsmentioning
confidence: 95%
“…Many epidemiological studies showed high incidence of this condition in female patients. The incidence of CRPS increases exponentially with age 5,6,9 . Risk of the smoker, patients with low bone mineral density (BMD) and individuals with pre‐existing anxiety or depression also have been reported 5 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations